Tax Awareness and Compliance: A Case Study of Instagram Celebrities in Palu City - Yeyen Masrianti Langkadja; Selmita Paranoan; Ni Made Suwitri Parwati; Rahayu Indriasari (UNIVED Press, 2026)
The purpose of this study is to describe and analyze the level of awareness and compliance of Instagram celebrities in Palu City in carrying out their tax obligations, while identifying the factors that influence them. The benefit of this study is as input for the tax authorities in formulating more adaptive socialization, education, and supervision strategies for digital taxpayer groups in the region, so that state tax revenues can be more optimal. This study uses a qualitative approach with a phenomenological method. Semi-structured in-depth interviews were used to collect data, with two Instagram celebrities selected using a purposive sampling technique, namely those who have a minimum of 30,000 followers on Instagram, actively carry out endorsement or paid promotion activities, and are domiciled or have economic involvement in the Palu City area. The results of this study found that the level of tax awareness and compliance among Instagram celebrities in Palu City is formed through the interaction between knowledge factors, trust in the government, and dynamic digital economic conditions. Increasing tax awareness and compliance needs to be realized through three main strategies, namely strengthening digital tax literacy, simplifying the tax administration system, and increasing public transparency.